From dust till drowned: the Holocene landscape development at Norderney, East Frisian Islands. (5th April 2021) - Schlütz, Frank; Enters, Dirk; Bittmann, Felix
Abstract: Within the multidisciplinary WASA project, 160 cores up to 5 m long have been obtained from the back-barrier area and off the coast of the East Frisian island of Norderney. Thirty-seven contained basal peats on top of Pleistocene sands of the former Geest and 10 of them also had intercalated peats. Based on 100 acclerator mass spectrometry (AMS) 14 C dates and analyses of botanical as well as zoological remains from the peats, lagoonal sediments and the underlying sands, a variety of distinct habitats have been reconstructed. On the relatively steep slopes north of the present island, a swampy vegetation fringe several kilometres wide with carrs of alder ( Alnus glutinosa ) moved in front of the rising sea upwards of the Geest as it existed then until roughly 6 ka, when the sea level reached the current back-barrier region of Norderney at around −6 m NHN (German ordnance datum). From then on for nearly 4000 years a changing landscape with a mosaic of freshwater lakes and fens existed within this area. It was characterised by various stands of Cladium mariscus (fen sedge), alternating with brackish reed beds with Phragmites australis (common reed) and salt meadows with Aster tripolium (sea aster), Triglochin maritima (sea arrowgrass), Juncus gerardii (saltmarsh rush) as well as mudflats with Salicornia europaea (common glasswort). As far as shown by our cores, this highly diverse, and for humans potentially attractive landscape was at least some 4 km wide and followed the coast for about 10 km. Before the rising sea caused diversification of habitats, wet heath as well as dry and dusty sand areas existed. In the course of time, parts of the wet heath turned into raised Sphagnum bogs under an oceanic precipitation regime before this diverse landscape was drowned by the rising sea and finally covered by marine sediments, while the earlier sediments and peats were partly eroded and redeposited.